Patriarchal Bargaining Strategies in The Secret Lives of Baba Segi’s Wives by Lola Shoneyin - Lorencia Sariani Tondang; Karina Hanum Luthfia (Universitas Islam Negeri Palopo, 2026)
This research examines the mechanisms of the patriarchal bargain within a polygamous household through a textual analysis of Lola Shoneyin’s novel The Secret Lives of Baba Segi’s Wives. Employing Deniz Kandiyoti’s framework of the